2016
DOI: 10.1299/mej.15-00441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of specimen size on ultimate compressive strength of Bio-coke produced from green tea grounds

Abstract: Various sizes of high-density biomass briquette, named 'Bio-coke,' were produced from spent green tea grounds. The mechanical properties at room temperature of the Bio-coke samples were investigated using a compression testing machine. From the results, the relationship between the specimen size of Bio-coke and the ultimate compressive strength at room temperature showed that the ultimate compressive strength depends on the specimen size of Bio-coke. The maximum value of the ultimate compressive strength among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…This tendency was particularly remarkable when the mixing ratio was 60wt.% or more. Mizuno et al also reported that the apparent density of Bio-coke decreases when the production temperature exceeds a certain temperature (Mizuno et al, 2016). Although the reason for this relationship remains incompletely understood, in the present study, an increase in volume, rather than a change in weight, caused the decrease in apparent density.…”
Section: Apparent Density Of Bio-cokesupporting
confidence: 56%
See 1 more Smart Citation
“…This tendency was particularly remarkable when the mixing ratio was 60wt.% or more. Mizuno et al also reported that the apparent density of Bio-coke decreases when the production temperature exceeds a certain temperature (Mizuno et al, 2016). Although the reason for this relationship remains incompletely understood, in the present study, an increase in volume, rather than a change in weight, caused the decrease in apparent density.…”
Section: Apparent Density Of Bio-cokesupporting
confidence: 56%
“…Compressive strength was measured with a compression testing machine (SHIMADU) (Mizuno et al, 2016). A load was applied from the top of the Bio-coke at a loading rate of 1.5 mm/min.…”
Section: Bio-coke Production and Testing Of Compressive Strengthmentioning
confidence: 99%
“…The compressive strength was affected by the diameter of the briquettes. When the diameter of the briquettes was reduced, the compressive strength increased (Mizuno et al, 2016). Table 3 shows the proximate and ultimate analyses based on different binder compositions.…”
Section: Bio-coke Productionmentioning
confidence: 99%
“…It is organic matter that comes from living organisms such as plant residue and animal waste. Biomass is a porous Energies 2021, 14, 6570 2 of 18 and fibrous material that consists of moisture, volatile matter, fixed carbon, ashes, and inorganic compounds such as Al, Si, K, Ca, and Na [4]. Biomass is a clean energy source that can partially substitute fossil fuels directly or be converted into gas, liquid, and solid fuels through different routes, namely, thermochemical and bioconversion.…”
Section: Introductionmentioning
confidence: 99%
“…A binding agent is necessary to improve the cohesion and bounding of the combustible materials to prevent the compressed material from crumbling. Compared to conventional coke, which has a value of 20-30 MJ/kg [16,17], the new, densified briquettes that were manufactured by Mizuno et al under high thermal compression (20 MPa and 200 • C) exhibited better properties, such as higher density, improved mechanical strength, and high calorific value [18]. Yustanti et al studied the maximal temperature of briquetting processes in order to generate maximal compressive strength.…”
Section: Introductionmentioning
confidence: 99%